Keberlanjutan Rehabilitasi Pekerja Seks Komersial (PSK) Studi Kasus : Pusat Pelayanan Sosial Karya Wanita (PPSKW) Mattiro Deceng Sudiang Makassar - Yudid Srywahyuni Silomba (Journal on Pustaka Cendekia Informatika, 2024)
This This research aims to determine the rehabilitation process for prostitutes at the PPSKW Mattiro Deceng rehabilitation center and the follow-up of PPSKW Mattiro Deceng towards prostitutes who have completed their rehabilitation period. By using descriptive qualitative research. The research results show that the rehabilitation process at PPSKW takes the form of providing guidance such as skills guidance (catering, cosmetology, sewing), social guidance, mental and religious/spiritual guidance. The implementation process was not optimal because it was influenced by awareness factors, both from PPSKW social workers, PPSKW instructors, and clients. Social workers and instructors do not strictly control the rehabilitation process activities, and clients do not participate in the rehabilitation process optimally. Post-rehabilitation (monitoring/follow-up) at PPSKW Mattiro Deceng was not carried out because the budget for monitoring was not available, but the only budget available was for the rehabilitation implementation process